KEFEKTIVITASAN MACROMEDIA FLASH PENDIDIKAN SEKS DALAM MEMPERSIAPKAN MASA PUBERTAS ANAK TUNAGRAHITA DI SLB B/C AL AZHAR WARU SIDOARJO - Dian Puspa Dewi (Universitas PGRI Madiun, 2016)
Sexual development of mental retardation’s children follows the physical development, thus experiencing a similar development with the normal ones. Those students have difficulty in understanding abstract information about the physical changes during puberty. Therefore, through the medium of learning macromedia flash, the sex education learning can be understood by them. This study aims to determine the effectiveness of using multimedia in teaching sex education as preparation for mental retardation’s students during puberty in SLB B/C SLB Al Azhar Waru Sidoarjo. The subjects were mental retardation’s students in that schools. Data collection techniques used in this research was shaped test objective tests. The design model used in this study is one group pretest-posttest design (treatment by subject design). Data analysis techniques used by the author in this research was a non-parametric analysis techniques that rank test Wilcoxon signed Sign marked tests (Wilcoxon Sign Rank Test). Based on the data analysis and discussion of the results of research, known that the Z count = -2070 with P = 0.038 at significance level of 5%. The results are smaller than 0.05 can be proven true. Based on those explanations it can be concluded that the alternative hypothesis which states